Favorable physiological and morphological effects of molybdenum nanoparticles on tobacco (Nicotiana tabacum L.): root irrigation is superior to foliar spraying - Chen, Juanni; Yin, Ying; Zhu, Yunsong; Song, Kun; Ding, Wei (Frontiers in Plant Science, 2023)
Introduction Nano fertilizers can provide efficient solutions to the increasing problem of nutrient deficiency caused by low availability. However, the most important prerequisite is to fully understand whether nanomaterials induce phytotoxicity in plants under a variety of different conditions. The mechanisms underlying interactions between molybdenum nanoparticles (Mo NPs) and plants with respect to their uptake and biological effects on crops are still not fully understood. Methods In this study, the impacts of Mo NPs over a range of concentrations (0, 25, and 100 μg/mL) on tobacco (Nicotiana tabacum L.) seedling growth were comparatively evaluated under foliar applications and root irrigation. Results The results indicated that more significant active biological effects were observed with root irrigation application of Mo NPs than with foliar spraying. The agronomic attributes, water content and sugar content of Mo NPs-exposed seedlings were positively affected, and morphologically, Mo NPs induced root cell lignification and more vascular bundles and vessels in tobacco tissues, especially when applied by means of root irrigation. Moreover, the photosynthetic rate was improved by 131.4% for root exposure to 100 μg/mL Mo NPs, mainly due to the increased chlorophyll content and stomatal conductance. A significant concentration-dependent increase in malonaldehyde (MDA) and defensive enzyme activity for the Mo NPs-treated tobacco seedlings were detected compared to the controls. Significantly improved absorption of Mo by exposed tobacco seedlings was confirmed with inductively coupled plasma mass spectrometry (ICP-MS) in tobacco tissues, regardless of application method. However, the accumulation of Mo in roots increased by 13.94 times, when roots were exposed to 100 mg/L Mo NPs, higher than that under treatment with foliar spray. Additionally, Mo NPs activated the expression of several genes related to photosynthesis and aquaporin processes. Discussion The present investigations offer a better understanding of Mo NPs-plant interactions in terrestrial ecosystems and provide a new strategy for the application of Mo NPs as nano fertilizers in crop production.